O insólito em Murilo Rubião : uma análise estilístico-comparativa d’O ex-mágico da Taberna Minhota - Aguiar, Marcela de Castro Ávila (2014)
The present study investigates the literary style of Murilo Rubião, whose work is considered by the critic as fantastic literature. After reading all the author’s short stories, having a deep look into his critical fortune and having critical-theoretical reading of fantastic literature, from its beginnings up to contemporary times, we concluded that his narratives correspond with the trivialized uncommon. Keeping this concept in perspective, we focused our research on the comparative analysis both extrinsic and intrinsic of three versions of the short story “The ex-magician of Minhota Tavern”, basing, respectively, on the theory of liquid modernity from Zigmunt Bauman, on the literary stylistic from Damaso Alonso and on portuguese language stylistic from Nilce Sant’Ana Martins. Other important bibliography sources to such stylistic analysis are the work of linguist José Lemos Monteiro and grammarians José Carlos de Azeredo e Napoleão Mendes de Almeida. Hence, we concluded that the writer Murilo Rubião not only anticipated characteristics of contemporary society in his work – such as the dilution of the subject identity – but also reflected about the very role of literature.